Aspek Hierarki Kebutuhan Tokoh Nirbita dalam Novel Sekotak Senja untuk Nirbita Karya Yupitawdr: Kajian Psikologi Sastra - Maria Elena Siagian; Haris Sutan Lubis; Emma Marsella (Departement of Mathematics Education, 2024)
This research discusses the hierarchy of needs of the character Nirbita in the novel Sekotak Senja untuk Nirbita by Yupitawdr, a study of Abraham Maslow's humanistic psychology. The hierarchy of needs states that humans fulfill low level needs to the highest needs to achieve satisfaction. These five needs, including: physiological, safety, social and love needs, are valued up to self-actualization. This research aims to describe the hierarchy of needs experienced by the character Nirbita in the novel Sekotak Senja untuk Nirbita by Yupitawdr. The research method used is a qualitative descriptive method with data collection techniques using library study techniques and note-reading techniques. The data in this research are in the form of quotations in the novel that show the hierarchy of needs of the character Nirbita in the novel Sekotak Senja untuk Nirbita by Yupitawdr. The data analysis technique in this research is a descriptive analysis technique which consists of grouping data related to the character Nirbita in the novel Sekotak Senja untuk Nirbita by Yupitawdr which is the main target in this research, describing and analyzing the data according to the research objectives, and drawing conclusions. Based on the results of the research, the character Nirbita in the novel Sekotak Senja untuk Nirbita by Yupitawdr has been fulfilled well. This research article can add insight and references for readers in understanding Abraham Maslow's hierarchy of needs in humanistic psychology.